Plasma Neurofilament Light Chain Levels Are Elevated in Children and Young Adults With Wolfram Syndrome - Eisenstein, Sarah A.; Boodram, Raveena S.; Sutphen, Courtney L.; Lugar, Heather M.; Gordon, Brian A.; Marshall, Bess A.; Urano, Fumihiko; Fagan, Anne M.; Hershey, Tamara (Frontiers in Neuroscience, 2022)
Wolfram syndrome is a rare disease caused by pathogenic variants in the WFS1 gene with progressive neurodegeneration. As an easily accessible biomarker of progression of neurodegeneration has not yet been found, accurate tracking of the neurodegenerative process over time requires assessment by costly and time-consuming clinical measures and brain magnetic resonance imaging (MRI). A blood-based measure of neurodegeneration, neurofilament light chain (NfL), is relatively inexpensive and can be repeatedly measured at remote sites, standardized, and measured in individuals with MRI contraindications. To determine whether NfL levels may be of use in disease monitoring and reflect disease activity in Wolfram syndrome, plasma NfL levels were compared between children and young adults with Wolfram syndrome (n = 38) and controls composed of their siblings and parents (n = 35) and related to clinical severity and selected brain region volumes within the Wolfram group. NfL levels were higher in the Wolfram group (median (interquartile range) NfL = 11.3 (7.8-13.9) pg/mL) relative to controls (5.6 [4.5-7.4] pg/mL). Within the Wolfram group, higher NfL levels related to worse visual acuity, color vision and smell identification, smaller brainstem and thalamic volumes, and faster annual rate of decrease in thalamic volume over time. Our findings suggest that plasma NfL levels can be a powerful tool to non-invasively assess underlying neurodegenerative processes in children, adolescents and young adults with Wolfram syndrome.